2000
DOI: 10.1034/j.1399-0004.2000.580504.x
|View full text |Cite
|
Sign up to set email alerts
|

The causes and consequences of random and non‐random X chromosome inactivation in humans

Abstract: X chromosome (X) inactivation is a remarkable biological process including the choice and cis-limited inactivation of one X, as well as the stable maintenance of this silencing by epigenetic chromatin alterations. The process results in females generally being mosaic for two populations of cells--one with each parental X active. In this review, we discuss recent advances in our understanding of how inactivation works, as well as the causes and clinical implications of deviations from random inactivation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
108
1

Year Published

2002
2002
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(111 citation statements)
references
References 126 publications
(135 reference statements)
1
108
1
Order By: Relevance
“…4G). The hypotrophic cells were clustered in a mosaic pattern, consistent with the origins of these clusters from single cells that have undergone X inactivation of the chromosome not containing the transgene (8). We then examined cardiomyocytes isolated from the hearts of Lef-1⌬20 transgenics.…”
Section: Resultsmentioning
confidence: 99%
“…4G). The hypotrophic cells were clustered in a mosaic pattern, consistent with the origins of these clusters from single cells that have undergone X inactivation of the chromosome not containing the transgene (8). We then examined cardiomyocytes isolated from the hearts of Lef-1⌬20 transgenics.…”
Section: Resultsmentioning
confidence: 99%
“…Increased XCI skewing has been observed in several human diseases with relevance to autism, such as Rett syndrome (Huppke et al, 2006;Knudsen et al, 2006) and X-linked mental retardation (MR) (Plenge et al, 2002). Increased skewing can result from multiple mechanisms including X-linked mutations and reduction in the pool of cells at the time of XCI in early embryogenesis (Brown et al, 2000). Skewed X inactivation was previously reported in autism female blood (Talebizadeh et al, 2005), but this report has yet to be independently replicated or examined in additional cell types.…”
Section: Introductionmentioning
confidence: 96%
“…Preferential XCI is an infrequent event in humans, which can be associated with conditions such as extensive X chromosome structural rearrangements, X-linked lethal traits and reduction of the number of embryonic precursor cells in the inner mass at the time of XCI commitment. 4,5 In extra-embryonic tissues of marsupials and mice, the X P is always inactivated. 3 In humans, conflicting data have been reported; of four recent studies, using the methylation assay of androgen receptor (AR), one reported X P preferential inactivation, 6 and three showed both random and preferential XCI.…”
Section: Introductionmentioning
confidence: 99%